Statistical Characteristics of Energetic Electron Pitch Angle Distributions in the Van Allen Probe Era: 1. Butterfly Distributions With Flux Peaks at Preferred Pitch Angles. Issue 3 (3rd March 2022) - Ozeke, L. G.; Mann, I. R.; Olifer, L.; Claudepierre, S. G.; Spence, H. E.; Baker, D. N.
Abstract: We present a statistical study on the properties of equatorial electron pitch angle distributions (PADs) in the Earth's outer radiation belt, for the first time based on particle measurements from the entire Van Allen Probes mission. A detailed selection criteria is used to identify intervals when flux measurements at energies from 0.2 to 3.4 MeV are available across a wide range of pitch angles close to the geomagnetic equatorial plane. To better characterize the shape of each pitch angle distribution, the flux data is fitted to functions of the equatorial pitch angle based on Legendre polynomials. Using this technique, we show that the shape of the PADs strongly depends on the particle's energy, location and geomagnetic activity. These results are used to identify the dominant physical processes responsible for creating PADs with different shapes. The results presented here mainly focus on the occurrence statistics and properties of butterfly PADs. Significantly, we find clear evidence that butterfly PADs have a peak flux that preferentially occurs at two distinct and discrete equatorial pitch angles, either 35° ± 5° or 65° ± 5°. Energy, L‐shell and magnetic local time variations indicate that the flux peaks at equatorial pitch angles ∼35° appear consistent with magnetopause shadowing, whilst those peaking at ∼65° may be associated with wave‐particle interactions. We also show that the flux at low and high pitch angles, for both butterfly and nonbutterfly PADs, remains remarkably well correlated even as the flux intensity varies by four orders of magnitude. Plain Language Summary: We present a statistical study on the properties and occurrence of equatorial electron pitch angle distributions (PADs) in the Earth's outer radiation belt based on particle measurements from the entire Van Allen Probes mission. The flux data is fitted to functions of the equatorial pitch angle. Using the PAD fits, the characteristics of PADs that have a local flux minimum near equatorial pitch angles of 90°, known as butterfly PADs, are determined. We find clear evidence that these butterfly PADs have a peak flux that preferentially occurs at two distinct and discrete equatorial pitch angles, either 35° ± 5° or 65° ± 5°. Energy, L‐shell and magnetic local time variations indicate that the butterfly PADs with flux peaks at equatorial pitch angles of ∼35° appear consistent with outer radiation belt electron loss through the magnetopause, whilst those peaking at ∼65° may be associated with wave‐particle interactions. We also show that the flux at low and high pitch angles, for both butterfly and nonbutterfly PADs, remains remarkably well correlated even as the flux intensity varies by four orders of magnitude. Key Points: Equatorial butterfly pitch angle distributions have preferred flux peaks at ∼35° or ∼65°, each occurring across different L and MLT ranges The depth of butterfly distribution dips tends to get smaller as the flux increases, inconsistent with growing off‐equatorial peaks From L*∼3 to ∼5, the flux at 90° is highly correlated with the flux at lower pitch angles, even as the flux varies by four orders of magnitude